Analisis Hubungan Caring Perawat Dengan Kepuasan Pasien Di Instalasi Gawat Darurat Rumah Sakit Umum Dr. Doris Sylvanus Palangka Raya Tahun 2019 - Eva Prilelli Baringbing (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Nursing services quality as an indicator of health service quality is a determining factor for the image of health service institutions in the public. Therefore, excellent nursing services should be realized in order do support the availability of quality health services and one of the indicators of nursing service quality is patient satisfaction, and nursing caring attitude as guarantees the quality of the nursing services. In the Emergency Room Installation, of dr. Doris Sylvanus Hospital still found nurses who were not informative, and nurses rarely explained to patients before taking nursing action, nurses did not want to accept patient coverage, and were quick to respond to nurses in helping patients, nurses did not pay attention to their patients, were not friendly. Patients and their families give poor ratings for the nurses. This study used a cross-sectional research design used an accidental sampling technique. Respondents of the trial study were 93 respondents representing patients at the emergency room at dr. Doris Sylvanus Hospital. Bivariate analysis that used chi square analysis. The result shown that there nursing nurses with patient satisfaction (p-value 0.000), the relationship with patient satisfaction.